Jenis Laba-laba Pada Pertanaman Jagung Di Kabupaten Minahasa Types of Spiders in Corn Plantations in Minahasa Regency - Fandi Marcel Rauwan; Ir. Daisy S. Kandowangko; Prof. Dr. Ir. Max Tulung,. MS (COCOS, 2019)
ABSTRACT Spiders (Araneae) are biological agents that are very potential in controlling insect pests in agricultural ecosystems. Pests are a cause of damage to plants, so pests that damage plants and can reduce production. Corn (Zea mays L) is one of the most important carbohydrateproducing food plants in the world, besides wheat and rice. The purpose of this study was to determine the type of spider in maize plantations in several villages in Minahasa Regency. This research was conducted in Sendangan Village, Sonder Subdistrict and Koyawas Village, West Langowan Subdistrict and Walewangko Village, West Langowan Subdistrict in Minahasa Regency. Materials and equipment used include 70% alcohol, mineral water plastic cups (240 ml), label paper, microscopes, Styrofoam food containers, skewers sticks, plastic ice cream bowls, stationery and corn planting areas. Pitfall traps are installed in the garden area, sampling is carried out after being installed for 2 days x 24 hours, spider sampling is carried out 3 times with an interval of one week per robbery per sampling. The results showed that (1) the type of spider that is in the planting of corn in several villages in Minahasa Regency has a very diverse species, the highest in Koyawas Village, then Walewangko Village, and the lowest in Sendangan Village and (2) The variety of cultivation methods and the circumstances surrounding maize play a role in determining the diversity of spider species. It is necessary to educate natural enemies on farmers so that farmers can reduce the use of chemicals that can threaten and kill natural enemies in the planting area. Keywords: spider, pest, corn